The system of flows and the restructuring of space elements of a geography of distribution - Hesse, Markus (ERDKUNDE, 2007)
Freight transport and logistics have long been neglected by geography and regional studies. This is surprising since several major spatial theories are based on the costs of overcoming space and thus, implicitly, on the characteristics of the distribution system. Falling transport costs and the communications revolution caused researchers to take this field for granted and, paradoxically, let it slip from focus. Changing global factors such as the expansion of world trade and the widening network of production systems have rightly rekindled interest in logistics and transport, also on the part of geographers. Restructuring of value-added chains has transformed the spatial needs, spatial dependence and spatial effectiveness of logistics. A new geography of distribution is evolving, expressing the interaction between commodity flows, location systems, and institutions. The growing mobility of goods and - recently - of location systems raises the question of how far logistics is working to loosen spatial ties and what the outcome will be.